2022
DOI: 10.3389/fvets.2022.816080
|View full text |Cite
|
Sign up to set email alerts
|

Shuttle Transfer of mRNA Transcripts via Extracellular Vesicles From Male Reproductive Tract Cells to the Cumulus–Oocyte Complex in Rabbits (Oryctolagus cuniculus)

Abstract: Semen is known to contain an ovulation-inducing factor (identified as a nerve growth factor, NGF) that shows a significant increase in ovulation after semen deposition in induced ovulatory species. However, the interplay between the male reproductive tract cells and oocyte maturation through messenger RNA (mRNA) cargo is yet to be investigated. Extracellular vesicles (EVs) from the primary culture of rabbit prostate (pEVs), epididymis (eEVs), and testis (tEVs) were isolated to examine their contents for severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…The functional effect of SP-EVs on the female gamete, nevertheless, has been poorly investigated. Only a study conducted in rabbits reported that EVs isolated from prostate, epididymis and testis primary cultures were able to interact with female gametes during IVM 49 . As the biological activity of EVs relies on the ability of target cells to bind and integrate them 57 , the first experiment aimed to determine the uptake of the two SP-EVs subsets by COCs during IVM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The functional effect of SP-EVs on the female gamete, nevertheless, has been poorly investigated. Only a study conducted in rabbits reported that EVs isolated from prostate, epididymis and testis primary cultures were able to interact with female gametes during IVM 49 . As the biological activity of EVs relies on the ability of target cells to bind and integrate them 57 , the first experiment aimed to determine the uptake of the two SP-EVs subsets by COCs during IVM.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrated that S-EVs and L-EVs isolated from porcine SP were able to bind CCs, but not oocytes, during IVM. Similarly, Abumaghaid et al (2022) examined the uptake of EV isolated from rabbit epididymal primary cultures by COCs, showing that EVs were able to bind CCs 49 . Several reports described the ability of EVs isolated from other reproductive biofluids, such as the follicular (Porcine 58 , 59 ; Equine 60 ; Bovine 61 ) and oviductal ones (Canine 62 ), to bind COCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that NGF, BDNF, and GDNF enhance oocyte maturation and early embryonic development ( Linher-Melville and Li, 2013 ). NGF plays an essential role in the female and male reproductive systems, and is known to promote ovulation while present in high concentrations in the semen of most species ( Maranesi et al, 2021 ; Abumaghaid et al, 2022 ). Previous studies have shown that BDNF/NT-4-TrkB signaling is required for follicle assembly and growth, as blockade of both BDNF and NT-4 impairs follicular assembly and increases oocyte death ( Ojeda et al, 2000 ; Spears et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%